2022
DOI: 10.1212/wnl.0000000000013129
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles Associated With Incident Ischemic Stroke

Abstract: Background:Women have higher lifetime risk of stroke than men, and metabolic factors seem more strongly associated with stroke for women than men. However, few studies in either men or women have evaluated metabolomic profiles and incident stroke.Methods:We applied liquid chromatography-tandem mass spectrometry to measure 519 plasma metabolites in a discovery set of women in the Nurses’ Health Study ([NHS], 454 incident ischemic stroke cases, 454 controls) with validation in two independent, prospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…A recent large‐scale prospective metabolomics study revealed that MetO was significantly associated with incident stroke, and its related metabolite score improved the prediction of the risk of incident ischemic stroke. 26 Another study confirmed the protective role of MetO reductase system to neurovascular inflammation in ischemic stroke, which attenuated ROS‐augmented NF‐κB activation in endothelial cells and protected against the oxidation of Met residues in the regulatory domain of calcium/calmodulin‐dependent protein kinase II (CaMKII). 27 Furthermore, the deficiency of MetO reductase A (MsrA) has been shown to promote vascular smooth muscle cell (VSMC) proliferation and neointimal hyperplasia through the extracellular signal‐regulated kinase 1/2 signaling pathway, 28 which were also pathological changes associated with MMD.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent large‐scale prospective metabolomics study revealed that MetO was significantly associated with incident stroke, and its related metabolite score improved the prediction of the risk of incident ischemic stroke. 26 Another study confirmed the protective role of MetO reductase system to neurovascular inflammation in ischemic stroke, which attenuated ROS‐augmented NF‐κB activation in endothelial cells and protected against the oxidation of Met residues in the regulatory domain of calcium/calmodulin‐dependent protein kinase II (CaMKII). 27 Furthermore, the deficiency of MetO reductase A (MsrA) has been shown to promote vascular smooth muscle cell (VSMC) proliferation and neointimal hyperplasia through the extracellular signal‐regulated kinase 1/2 signaling pathway, 28 which were also pathological changes associated with MMD.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have discussed the relationship between MetO and cerebrovascular disease. A recent large‐scale prospective metabolomics study revealed that MetO was significantly associated with incident stroke, and its related metabolite score improved the prediction of the risk of incident ischemic stroke 26 . Another study confirmed the protective role of MetO reductase system to neurovascular inflammation in ischemic stroke, which attenuated ROS‐augmented NF‐κB activation in endothelial cells and protected against the oxidation of Met residues in the regulatory domain of calcium/calmodulin‐dependent protein kinase II (CaMKII) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The link between MetO and cerebrovascular disease has been shown. A recent large prospective study on metabolomic characteristics of ischemic stroke found a significant association between MetO and incident stroke, with higher levels being associated with increased risk ( Balasubramanian et al, 2022 ). Another study demonstrated that betaine could decrease proinflammatory cytokine production and reduce oxidative stress after brain ischemia and reperfusion injury by upragulating MetO reductase ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a major derivative of methionine oxidation with ROS by a two-electron dependent mechanism [ 149 ]. Balasubramanian et al [ 95 ] reported an association between the methionine sulfoxide and the increased risk of incident stroke. Another study conducted by Li et al [ 150 ] observed a neuroprotective impact in ischemia/reperfusion injuries when when an increase in methionine sulfoxide reductases enzymes occurred following betaine administration; the methionine sulfoxide reductases enzymes.…”
Section: Oxidative Protein Modificationsmentioning
confidence: 99%